2006
DOI: 10.1002/art.21993
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coping skills on health‐related quality of life in patients with systemic lupus erythematosus

Abstract: Objective. To identify coping strategies used by patients with systemic lupus erythematosus (SLE), and to assess the influence of main clinical and coping variables on health-related quality of life (HRQOL). Methods. We administered the Coping Orientation to Problems Experienced and the Short Form 36 questionnaire to a group of 144 patients with SLE and a group of 129 healthy controls. At the time of the psychological assessment, all patients underwent a complete clinical and laboratory evaluation. Results. SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 29 publications
1
37
2
Order By: Relevance
“…Similarly, another study (Rinaldi et al, 2006) found that patients with sle used mostly strategies such as acceptance and turning to religion, and less strategies such as planning, suppression of competing activities, restraint coping, focusing on and venting of emotion, along with strategies focused on the problem, compared with healthy controls.…”
Section: Copingmentioning
confidence: 86%
See 3 more Smart Citations
“…Similarly, another study (Rinaldi et al, 2006) found that patients with sle used mostly strategies such as acceptance and turning to religion, and less strategies such as planning, suppression of competing activities, restraint coping, focusing on and venting of emotion, along with strategies focused on the problem, compared with healthy controls.…”
Section: Copingmentioning
confidence: 86%
“…Although most studies agree that there are no adaptive or maladaptive strategies, the suitability of these depend on the situation that must be coped with (Rinaldi et al, 2006). The active coping is considered the best predictor of qol preservation in both the active and inactive phase of the disease (Dobkin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No study to date has examined how coping cognitions specific to pain may influence important outcomes, such as pain, stiffness, fatigue, and mood, in SLE patients. Past studies in patients with SLE have demonstrated that patients' general coping strategies and perceptions of control (i.e., not specifically related to SLE pain) are related to SLE disease activity (2,6 -8), physical functioning (9), psychological functioning (2,10), and other measures of quality of life (11). Two pain coping cognitions that may be particularly important to consider in patients with SLE are self-efficacy for pain control and pain catastrophizing.…”
Section: Introductionmentioning
confidence: 99%